The three-point start - Glover, D. (Track Coach, 2019)
Coach Glover has achieved good success using a 3-point start for some of his sprinters. He sets out the whys and wherefores of this controversial starting technique for middle and high school sprinters. Many sprinters and hurdlers in middle school and high school have difficulty generating enough power out of the crouch blocks (four point start), to maintain the proper angle during the "gun" phase of the start. These words were published in the Athletic Journal in May of 1984. The article was written as an attempt to promote the use of the 3-point start for some athletes in middle school and high school. The article was entitled Stand up Starts. The article was written because, at that time, the author taught weight training in Physical Education and also coached track & field at the senior high level. This combination of duties, gave him the opportunity to observe the huge discrepancy in strength and coordination betweenan average 13-year-old boy/girl.